JUSTIFICATION AND DESIGN OF OPERATING PARAMETERS OF VIBRATING DOSERS FOR FLOUR PACKAGING - Підлісний, Віталій; Семенов, Олександр; Федорів, Віктор; Мазорчук, Ірина (SWorldJournal, 2026)
The article presents a comprehensive study on the design and optimization of the operational performance of vibratory volumetric feeders integrated into high-performance wheat flour packaging lines. Based on a systematic analysis of the external environme